Access to E-Journals: Need and Impact of Users Training - Chand, Prakash; Nishy, P; Mahesh, G. (Digital Libraries: Achievements, Challenges and Opportunities, 2006)
The paper presents an analysis of feedback taken from participants of trainers training programme of Council of Scientific and Industrial Research (CSIR), India, for 38 national R&D laboratories/institutions of CSIR. The study reveals the need of distribution and display of publicity material at prominent places of user institutions; training to end users requires repetitive and dynamic order; and library portal be the linking hub of all the information resources. The paper also covers web based monitoring and common search interface system developed for control and user friendliness.